The nephelauxetic effect of Eu(iii)–N-donor compounds probed using fluorescence spectroscopy—further evidence for covalence?. (26th September 2016) - Wagner, Christoph; Ruff, Christian; Müllich, Udo; Geist, Andreas; Panak, Petra J.
Abstract : A new correlation for the identification of Eu(iii ) N-donor complexes in aqueous and organic media is introduced, exhibiting new information on the nature of Eu(iii ) bonding. Abstract : The 7 F0 emission bands of Eu(iii )–N-donor complexes are investigated using time resolved laser fluorescence spectroscopy (TRLFS) and fluorimetry. The observed bathochromic shifts resulting from the complexation of Eu(iii ) with N-donor ligands are considerably more pronounced than those observed for hard oxygen donor ligands. The magnitude of these shifts results from a strong nephelauxetic effect caused by the interaction of Eu(iii ) with N-donor ligands. Since the extent of the nephelauxetic effect is correlated with the degree of covalence in a metal–ligand bond, the results prove a significant share of covalence in the Eu(iii )–N-donor bonds in addition to electrostatic interactions. Furthermore, a linear correlation between the shift of the 7 F0 emission band of the Eu(iii ) complexes with BT(B)P/BTPhen ligands relative to the Eu(iii ) aquo ion and the number of N-donors in the first coordination sphere of Eu(iii ) is established: CNL = 0.109·Δ ν + 0.134, [Δ ν ] = cm −1 . Taking into account the known denticity of BTP/BTBP/BTPhen ligands the stoichiometry of the investigated complexes is easily determined by using the above equation.